2013
DOI: 10.1111/ajt.12091
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage as a Tool to Predict, Diagnose and Understand Bronchiolitis Obliterans Syndrome

Abstract: Bronchiolitis obliterans syndrome (BOS), a condition of irreversible small airway fibrosis, is the principal factor limiting long-term survival after lung transplantation. Bronchoscopy and bronchoalveolar lavage (BAL), techniques central to lung transplant clinical practice, provide a unique opportunity to interrogate the lung allograft during BOS development and identify potential disease mechanisms or biomarkers. Over the past twenty years, numerous studies have evaluated the BAL cellular composition, cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 114 publications
4
66
0
Order By: Relevance
“…BAL cells and proteins have long been studied in the context of pulmonary diseases. In lung transplantation, in particular, BAL parameters have been shown to correlate with allograft dysfunction [7]. However, concerns exist regarding the lack of standardization of BAL techniques, which hinders the potential clinical utility of measured BAL components and limits comparison and The results of this study demonstrate reproducible differences between sequential fractions of BAL.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…BAL cells and proteins have long been studied in the context of pulmonary diseases. In lung transplantation, in particular, BAL parameters have been shown to correlate with allograft dysfunction [7]. However, concerns exist regarding the lack of standardization of BAL techniques, which hinders the potential clinical utility of measured BAL components and limits comparison and The results of this study demonstrate reproducible differences between sequential fractions of BAL.…”
Section: Discussionmentioning
confidence: 65%
“…Examination of the cellular composition and protein constituents in the BAL provides a unique window into the microenvironment of the lung. In lung transplantation, BAL proteins have been proposed as potential biomarkers of acute rejection [3][4][5][6] and chronic lung allograft dysfunction (CLAD) [7]. However, small sample sizes, lack of control for potential confounders and lack of standardization related to BAL collection and handling have all been proposed as sources of variability between studies [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that defensin levels were increased in bronchoalveolar lavage fluids in many inflammatory lung diseases including cystic fibrosis, pneumonia, tuberculosis, and bronchiolitis obliterans (18)(19)(20)(21)(22). On the other hand, exposure of airway epithelium to Th2 cytokines including interleukin 4 and 13 significantly reduces BD-2 mRNA synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneous nature of CLAD, it comes to no surprise that at this moment, there are no universally applied biomarkers for BOS diagnosis. Broncho-alveolar lavage (BAL) analysis may provide insights in the lung micro-environment (27). Using BAL, the first important markers for BOS came to light, which included neutrophils and markers of neutrophil activation (CXL-8, MMP-9) (28).…”
Section: Risk Factors and Mechanisms Of Bosmentioning
confidence: 99%